Indian Administration;A Foundation of Governance - Radhakrishnan Sapru (Sage, 2018)
Indian Administration: A Foundation of Governance offers a modern introduction to the structure and functioning of Indian public administration. The text has been developed keeping in mind the various conceptual shifts in the idea and practice of governance and its effects at both domestic and global levels.